POTENSI PENGEMBANGAN TOD PADA SIMPUL TRANSPORTASI MODA KERETA API (Studi Kasus: Provinsi Jawa Barat, Indonesia) - Herawati Zetha Rahman; Azaria Andreas; Imam Hagni Puspito; Perdana Miraj Sejatiguna; Nina Kade Nirmala (Jurnal Infrastruktur, 2021)
Rail is one of the land transportation modes that are widely used in many areas. Along with this, the train station as the central of movement especially in urban area can be developed as the central of urban activities by maximizing the use of space in the station and its surrounding area which is integrated with the development of properties high density and other public facilities. At present, the majority of train stations in Indonesia only serve as up and down of passengers without additional functions. For this reason, an effort is needed to maximize the potential of the station through the Transit Oriented Development (TOD) approach. The development of TOD at the train station can shorten the distance of train users, creating lower cost, time and energy efficiency so as to improve the quality of life in urban areas. Besides that, by increasing the station's function to TOD, it is expected to be able to reduce the maintenance costs of the station itself through the additional of functions that can generate revenue. In order to optimize the function of the train station, especially in urban areas, this study was carried out to make a conception of regional development with the TOD concept based on the train station. This study uses a qualitative approach with the study area in 5 provinces in Java (outside the BPTJ work area), and data collection is done using the purposive sampling method. The result is, station that has the potential to be developed into a transit-based area, among others is Bandung Station (West Java)